Structure of an endogenous yeast 26S proteasome reveals two major conformational states - Luan, Bai; 栾白; Huang, Xiuliang; 黄修良; Wu, Jianping; Mei, Ziqing; Wang, Yiwei; Xue, Xiaobin; Yan, Chuangye; Wang, Jiawei; Finley, Daniel J.; Shi, Yigong; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
The eukaryotic proteasome mediates degradation of polyubiquitinated proteins. Here we report the single-particle cryoelectron microscopy (cryo-EM) structures of the endogenous 26S proteasome from Saccharomyces cerevisiae at 4.6- to 6.3-Å resolution. The fine features of the cryo-EM maps allow modeling of 18 subunits in the regulatory particle and 28 in the core particle. The proteasome exhibits two distinct conformational states, designated M1 and M2, which correspond to those reported previously for the proteasome purified in the presence of ATP-γS and ATP, respectively. These conformations also correspond to those of the proteasome in the presence and absence of exogenous substrate. Structure-guided biochemical analysis reveals enhanced deubiquitylating enzyme activity of Rpn11 upon assembly of the lid. Our structures serve as a molecular basis for mechanistic understanding of proteasome function.